Non-Observance of the Maxims in Diary of a Wimpy Kid - Nico Harared (Journal of English Language and Culture, 2017)
The purpose of this research to discover non-observance of the maxim in Diary of a Wimpy Kid. The data is taken from Diary of a Wimpy Kid movie. In collecting the data,the writer uses non-participatory method. In analyzing data, the writer applies the pragmatic identity method. The main theory proposed by Grice as cited in Thomas (1995, p. 64) and supported by other theories related in analyzing the non-observance of the maxims, whether it is flouting a maxim, violating a maxim, infringing a maxim, opting out of a maxim, and suspending a maxim. In reporting the result of the analysis, the writer uses formal and informal method of presentation.The findings shows that non-observances of the maxim mostly happensbetween the characters that have close relation and according to goal and it is depend on the context of thesituation. Keywords: non-observance, maxim, flouting maxim and violating maxim